2012
DOI: 10.4236/as.2012.35084
|View full text |Cite
|
Sign up to set email alerts
|

Macro-nutrients in edible parts of food crops in the region of Moanda, Gabon

Abstract: The assessment of nutritive foodstuffs quality is an important step in the estimation of dietary intake of metals. This study aimed to assess accumulation and the daily intake of macro-elements magnesium, calcium, potassium and sodium in edible parts of plants grown in Moanda area. The ranges of concentrations were 246 - 5645 mg/kg, 1167 - 35105 mg/kg, 158 - 12563 mg/kg and 88 - 795 mg/kg for Mg, Ca, K and Na, respectively. Mg and K levels were significantly higher in fruits than in tubers. The trend of accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…Gnetum is a vegetable and nut fruit used for health-care; the leaves are common vegetables and spices in Nigeria, Cameroon, Central Africa, Congo, Angola, and Southeast Asia, and they are sold to Europe, the USA, and Japan. In Southeast Asia, Gnetum is cultivated to produce nuts, and the output of a mature plant reaches 80–100 kg. , In addition, Gnetum species reportedly produce many important bioactive compounds (e.g., flavonoids and stilbenoids) that are used in traditional medicines in many countries, having hypotensive, antioxidant, anticancer, and antibacterial effects. Because of their economic value, there has been considerable interest in the introduction, domestication, and cultivation of Gnetum species in Africa and Southeast Asia . Seed propagation is currently one of the main methods of reproducing Gnetum species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gnetum is a vegetable and nut fruit used for health-care; the leaves are common vegetables and spices in Nigeria, Cameroon, Central Africa, Congo, Angola, and Southeast Asia, and they are sold to Europe, the USA, and Japan. In Southeast Asia, Gnetum is cultivated to produce nuts, and the output of a mature plant reaches 80–100 kg. , In addition, Gnetum species reportedly produce many important bioactive compounds (e.g., flavonoids and stilbenoids) that are used in traditional medicines in many countries, having hypotensive, antioxidant, anticancer, and antibacterial effects. Because of their economic value, there has been considerable interest in the introduction, domestication, and cultivation of Gnetum species in Africa and Southeast Asia . Seed propagation is currently one of the main methods of reproducing Gnetum species.…”
Section: Introductionmentioning
confidence: 99%
“…In Southeast Asia, Gnetum is cultivated to produce nuts, and the output of a mature plant reaches 80−100 kg. 2,3 In addition, Gnetum species reportedly produce many important bioactive compounds (e.g., flavonoids and stilbenoids) that are used in traditional medicines in many countries, having hypotensive, antioxidant, anticancer, and antibacterial effects. 4−7 Because of their economic value, there has been considerable interest in the introduction, domestication, and cultivation of Gnetum species in Africa and Southeast Asia.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The order of nutrient uptake differs from that verified by Rozane et al (2011) for the same genotypes, since they observed that N and K were required, as well as from that reported by Freitas et al (2011) for Nota-10 star fruit cultivar, with N and K being the most required, both studies were conducted under hydroponics. However, Ondo et al (2012) observed that Ca, followed by potassium, are the most exported nutrients in fruit plants in general. Variations in the order of nutrient uptake in fruit trees are commonly reported in the literature, when different genetic materials and cultivation techniques are used, in addition to the cultivation time such as for guava (Augostinho et al, 2008;Franco et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their striking evolutionary divergence, Gnetum species are an important medical, grain, and oil crop in many countries (Deng et al., 2016). In Africa, G. africanum and G. buchholzianum are widely used as vegetables (Ondo, Biyogo, Olluimboulou, Eba, & Omva‐Zue, 2012; Ondo, Biyogo, Olluimboulou, Eba, & Omva‐Zue, 2012), and is considered an important cash crop in backward areas in Africa (Ali, Assanta, & Robert, 2011; Moise et al., 2012). Additionally, many species of Gnetum are rich in bioactive compounds which can be used for medical purposes (Deng et al., 2016; Deng, Liu et al., 2016), Gnetum are cultivated as healthy vegetables in central Africa for export, and has became the second only to banana ( Musa X paradisiaca L.) planting and snail rearing (Lambert & Ozioma, 2012).…”
Section: Introductionmentioning
confidence: 99%